Elimination of zinc ions from aqueous solution by a hydroxylapatite-biochar composite material with the hierarchical porous microstructures of sugarcane waste. (15th August 2022) - Zhu, Zongqiang; Wu, Yuqing; Hu, Chengzhi; Zhang, Lihao; Ding, Hui; Zhu, Yinian; Fan, Yinming; Deng, Huan; Zhou, Xiaobin; Tang, Shen
Abstract: A hydroxylapatite-biochar composite material with the hierarchical porous microstructures of sugarcane top internodes (HAP/C-SC) was produced by carbonizing sugarcane top stalks, an agricultural waste residue, and then soaking them in limewater and (NH4 )2 HPO4 solution in turns. The HAP/C-SC with the surface area of 8.52–28.44 m 2 /g inherited various macropores from parallel vessels, thick-walled cells of sclerenchyma, thin-walled cells of storage parenchyma, and pits in cell and vessel walls of sugarcane top stalks. When the initial Zn 2+ concentration is 5–400 mg/L, the Zn 2+ absorption capacity of HAP/C-SC is 19.91, 22.54, and 25.37 mg/g at 25 °C, 35 °C, and 45 °C, respectively, which is equivalent to the Zn 2+ absorption capacity of synthetic nano-hydroxyapatite. The HAP/C-SC showed a good removal performance for Zn cations, and the adsorption followed Langmuir model and pseudo-second-order kinetic model well. The Zn-containing hydroxylapatite solid solutions [(Znx Ca1‒x )5 (PO4 )3 (OH)] were considered to be the key mechanism for Zn 2+ elimination, which formed through the co-action processes including adsorption, ion exchange (x = 0.06–0.12) and dissolution-precipitation (x = ∼0.27). The M(2) vacancy sites are believed to be energetically more favorable for the Zn ion occupation. The substitution and occupation of M(2) sites by Zn ions may be affected by spatial constraints. Graphical abstract: Image 1 Highlights: One kind of porous biomorph-genetic composite of HAP/C was prepared. The material retained the hierarchical porous microstructure of sugarcane top. The material has different pores from vascular, parenchyma, sclerenchyma and pits. The elimination capacity for Zn(II) is comparable to nano-hydroxyapatite. The adsorption followed the pseudo-second-order equation and Langmuir isotherm.